INDEKS STABILITAS AGREGAT TANAH PADA PERKEBUNAN TEH BERBASIS SLOPE DAN UMUR TANAMAN DI KECAMATAN GUNUNG TALANG KABUPATEN SOLOK - Dendy Detafiano Prakasa Afner; Aprisal Aprisal; Yulnafatmawita Yulnafatmawita (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Land-use change from the forest into tea plantation in Solok Regency in 1983 has decreased the area of forests in Gunung Talang District. Clearing up the forest at the beginning for tea plantation could worsen the physical and chemical conditions of the soil. One of which is soil aggregate stability that is very dynamic and can influence other soil physical properties. This study was aimed to determine soil Aggregate Stability Index (ASI) at tea plantations. Soil samples was taken at a depth of 0-20 cm from five different slopes (0-8% (A), 8-15% (B), 15-25% (C), 25-45% (D), and> 45% (E)) and at two crop ages (10 and 35 years old). The results showed that the soil aggregate stability index at tea plantations ranged from stable to very stable. It tended to decrease by increasing slope percentage at each of crop age, Between the ages, it showed higher ASI at 35 years old crop age under relatively flat (0-8%) and very steep (>45%) areas.